Determinants of the varied profiles of Plasmodium falciparum infections among infants living in Kintampo, Ghana - Botwe, Akua Kyerewaa; Oppong, Felix Boakye; Gyaase, Stephaney; Owusu-Agyei, Seth; Asghar, Muhammad; Asante, Kwaku Poku; Färnert, Anna; Osier, Faith (Malaria journal, 2021)
Understanding why some infants tolerate infections, remaining asymptomatic while others succumb to repeated symptomatic malaria is beneficial for studies of naturally acquired immunity and can guide control interventions. This study compared demographic, host and maternal factors associated with being either parasite negative or having asymptomatic infections versus developing symptomatic malaria in the first year of life.
Gesehen am 14.09.2022